Clinical particulars of acute coronary syndrome course in patients with COVID-19 - Nadezhda V. Izmozherova; Artem A. Popov; Andrey I. Tsvetkov; Leonid I. Kadnikov; Vladislav E. Ispavskii; Muraz A. Shambatov (Alʹmanah Kliničeskoj Mediciny, 2023)
Background: Cardiovascular complications of COVID-19 result in challenges for differential diagnosis, patients referral and treatment, which negatively affect the outcomes.